THE INFLUENCE OF WORD OF MOUTH, BRAND AWARENESS AND PRICE PERCEPTION ON PURCHASE INTENTION: A STUDY OF MAGOMAGOO DESSERT MANADO - Mambu, Abigail Kayla Briana; Worang, Frederik G.; Rumokoy, Lawren J. (Jurnal EMBA : Jurnal Riset Ekonomi, Manajemen, Bisnis dan Akuntansi, 2025)
This study assesses the simultaneous and partial influence of Word of Mouth (WOM), Brand Awareness (BA), and Price Perception (PP) on the Purchase Intention (PI) of consumers for Magomagoo Dessert in Manado. The research addresses a key gap in understanding specific consumer behavior within the highly competitive food and beverage (dessert) industry. Utilizing a descriptive quantitative research approach, data was collected from a sample of 100 respondents (followers of Magomagoo Dessert Manado’s Instagram account) via an online questionnaire. The analysis employed multiple linear regression and classical assumption tests. The findings confirm that WOM, Brand Awareness, and Price Perception all have a significant and positive influence on consumer Purchase Intention, both individually and collectively. The results indicate that strategically enhancing positive word-of-mouth, strengthening brand recognition, and ensuring fair pricing are critical factors for stimulating consumer purchase intention.   Keywords: Word-Of-Mouth, Brand Awareness, Price Perception, Purchase Intention